PENGARUH PENGETAHUAN INVESTASI, PERSEPSI RISIKO, DAN PERSEPSI KONTROL PERILAKU TERHADAP MINAT INVESTASI SAHAM - Ngadino, Satrio Wibowo Edi; Fahreza, Muhammad (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2020)
This study aims to determine and analyze the impact of investment knowledge, perceived risk, and perceived behavioral control of the Indonesian stock investment intention. The research data is the data collected through questionnaires starting from 12 April 2018 until 30 April 2018. The population in this study are all people who have never invested shares, independent income, and located in the area of Jakarta. The sampling method used is the Roscoe method with the number of members of the sample at least ten times the number of variables studied. So that the minimum number of samples in this study were 40 respondents, and the number of respondents used in this study was 100 respondents. The analytical method used in this study using multiple linear regression analysis using SPSS version 21 (Statistical Package for Social Sciences). The results showed that the investment knowledge affect the stock investment intention, the perceived risk affect the stock investment intention, the perceived behavioral control affect the stock investment intention, and the investment knowledge, perceived risk, perceived behavioral control affect the stock investment intention simultaneously.